Indirect costs of arterial hypertension and its complications - Choromańska, Anna; Szumiał, Szymon; Czerw, Aleksandra Izabela (Journal of Education, Health and Sport, 2019)
Arterial hypertension (AH) and related cardiovascular complications are considered to be a global factor of morbidity and mortality of the adult population. Every year, over 9 million people die prematurely due to arterial hypertension and its complications, of which about one third of patients are unaware of their illness. The article presents a study on the indirect costs of hypertension and its complications in Poland. The analysis material comes from data obtained from the Social Insurance Fund (ZUS) and Statistics Poland (GUS) on the subject of GDP in 2016 -2017 and data on the percentage of working-age people and the general population for 2016 -2017. The total cost of absenteeism as a result of AH and its complications in 2016-2017 amounted to PLN 585,044,909.70. The total cost of presenteeism as a result of AH and its complications in 2016-2017 was PLN 284,494,461.54. Total indirect costs of informal care due to AH and its complications in 2016-2017– 30,386,446.74 PLN. Total indirect cost of permanent or temporary incapacity to work due to AH and its complications in 2016-21017 was 3.834.367.026,86 PLN. The final indirect cost of deaths in the amount of PLN 255,050,903.29 was obtained. Taking into account all categories of indirect costs (absenteeism, presenteeism, informal care, permanent and partial incapacity to work and premature deaths), total indirect costs of AH and its complications in Poland in 2016 amounted to PLN 2,722,988,728.26, representing a loss of 0.14% of GDP on a yearly basis. The indirect cost of AH and its complications in 2017 amounted to PLN 2,621,405,923.16, representing a loss of 0.13% of GDP on a yearly basis